Contour prolongation in Steven Gellman's Concerto for Viola and Orchestra (2004): Tracing the narrative of the ego and alter-ego - Loback, Jamie (University of Ottawa (Canada), 2009)
This thesis illustrates a narrative paradigm consisting of the ego and alter-ego, manifested within the thematic content of Gellman's Concerto for Viola and Orchestra. I invoke contour theory as my primary analytical tool, which I combine with Schenkerian techniques to highlight the possibilities for contour prolongation at the foreground, middleground, and background levels. I support my analysis based on various types and combinations of accent, harmony, and voice leading. Chapter one contains Gellman's biographical information, while chapter 2 provides the methodology of my analytical approach based on the contour models devised by Marvin, Laprade, and Morris. Regarding accent and prolongation, I reference the work of Roeder and Straus, respectively. In chapters three and four, I analyse the first two movements providing a contour/prolongational analysis of the primary thematic material. Chapter five summarises these relationships and investigates the implications for research in the third movement of the Gellman's composition. Keywords: Steven Gellman, Concerto for Viola and Orchestra, Contour, Theme, Contour Relations, Prolongation, Contour Prolongation, Narrative, Ego, Alter-ego, Elizabeth West Marvin, Paul A. Laprade, Robert D. Morris, Joseph Straus, John Roeder, Heinrich Schenker
Keywords: Music.